Crossed Pathways for Radiation-Induced and Immunotherapy-Related Lung Injury - Zhang, Zengfu; Zhou, Jialin; Verma, Vivek; Liu, Xu; Wu, Meng; Yu, Jinming; Chen, Dawei (Frontiers in Immunology, 2021)
Radiation-induced lung injury (RILI) is a form of radiation damage to normal lung tissue caused by radiotherapy (RT) for thoracic cancers, which is most commonly comprised of radiation pneumonitis (RP) and radiation pulmonary fibrosis (RPF). Moreover, with the widespread utilization of immunotherapies such as immune checkpoint inhibitors as first- and second-line treatments for various cancers, the incidence of immunotherapy-related lung injury (IRLI), a severe immune-related adverse event (irAE), has rapidly increased. To date, we know relatively little about the underlying mechanisms and signaling pathways of these complications. A better understanding of the signaling pathways may facilitate the prevention of lung injury and exploration of potential therapeutic targets. Therefore, this review provides an overview of the signaling pathways of RILI and IRLI and focuses on their crosstalk in diverse signaling pathways as well as on possible mechanisms of adverse events resulting from combined radiotherapy and immunotherapy. Furthermore, this review proposes potential therapeutic targets and avenues of further research based on signaling pathways. Many new studies on pyroptosis have renewed appreciation for the value and importance of pyroptosis in lung injury. Therefore, the authors posit that pyroptosis may be the common downstream pathway of RILI and IRLI; discussion is also conducted regarding further perspectives on pyroptosis as a crucial signaling pathway in lung injury treatment.